JAPANESE DEMAND FOR TOURISM IN INDONESIA: AN ECONOMETRIC MODELING AND FORECASTING - D.S. PRIYARSONO (ASEAN Journal on Hospitality and Tourism, 2011)
The contribution of Japanese tourists to the total number of foreign tourists visiting Indonesia has always been very significant. Tourism authorities as well as tourism related enterprises therefore are normally interested in finding the factors affecting Japanese demand for tourism in Indonesia. This study attempts to analyze factors that influence Japanese demand for tourism in Indonesia by utlizing an econometric modeling. The model that results from this analysis is then used to forecast the number of Japanese tourists visiting Indonesia in 2011- 2015. The most significant factor that affected the Japanese demand for tourism in Indonesia was Japan's GDP.